Cerebral Venous Sinus Thrombosis: Successful Treatment of Two Patients Using the Penumbra System and Review of Endovascular Approaches. Issue 2 (April 2015) - Liao, Weihua; Liu, Yunhai; Gu, Wenping; Yang, Jie; Chen, Changqing; Liu, Fan; Zeng, Feiyue; Wang, Xiaoyi
Cerebral venous sinus thrombosis (CVST) is an uncommon but potentially life-threatening condition. When showing resistance to treatment or a malignant progression despite anticoagulant therapy, endovascular interventional treatment is of help. The Penumbra System (PS), a novel thrombectomy device specifically designed to remove the thrombus in acute ischemic stroke, also proved to be an effective device for mechanical recanalization of CVST. We first reported two cases successfully treated using the PS in the management of intractable CVST in Asia, and analyzed the technical differences of use of the device through a systematic review of the literature. One patient underwent mechanical thrombectomy of the thrombosed superior sagittal sinus using the 0.054-inch PS catheter when direct pharmacological thrombolysis failed. The other patient underwent mechanical thrombectomy using the 0.041-inch PS catheter with adjuvant local pharmacological thrombolysis. Literature reports on the use of the PS in patients with CVST were reviewed. Successful venous recanalization was achieved using the PS. The patients improved symptomatically following the intervention. Literature reports showed that the PS can be successfully applied for treatment of CVST, though the methods used previously were diverse. The PS has proved to be effective in the rapid recanalization of CVST, but different treatment techniques exist. The solution to these problems depends on more clinical trials as well as further improvements to devices.